Inokulasi Mikrokapsul Bakteri Rizosfer Dari Tanah Erupsi Sinabung Sebagai Booster Pertumbuhan Bibit Kopi Robusta (Coffea canephora L.) - Tarigan, Rico Kris Hadinata; Warsito, Kabul; Setiawan, Andi (Journal of Natural Sciences, 2025)
This study evaluated the effect of rhizosphere bacteria microcapsule fertilizer and chicken manure fertilizer on the growth of robusta coffee seedlings (Coffea canephora L.) in an effort to develop environmentally friendly superior seedlings. Using a two-factorial Completely Randomized Design with 16 treatments and 5 replications, variations in doses of chicken manure fertilizer (0, 100, 200, 300 grs) and rhizosphere bacteria microcapsules (0, 5, 7.5, 10 grs) were tested. The results showed that a dose of 100 grs of chicken manure fertilizer (K1) gave the best growth response in all parameters, with plant height reaching 51.40 cm at 4 BSPT, an increase of 44.8% compared to the control. Root length showed a non-linear response pattern, where K1 produced the highest root length (30.68 cm²) and the highest dose (K3) produced the lowest root length (24.36 cm²). The number of leaves and leaf area also increased significantly in the K1 treatment compared to the control. Rhizosphere bacteria microcapsules provide positive effects through root growth stimulation and phytohormone production that increases nutrient absorption efficiency. These findings emphasize the importance of optimizing the dosage of chicken manure fertilizer and rhizosphere bacteria microcapsules for sustainable robusta coffee seedling growth.